Laterals in Spanish–English bilinguals: patterns of separation and interlingual influences - Yavaş, Mehmet; Suner, Michele (Journal of Monolingual and Bilingual Speech, 2022)
Patterns of production of Spanish and English laterals by early sequential Spanish–English bilinguals (L1 and L2 respectively in the order of acquisition) were investigated. A total of 25 early Spanish–English bilinguals, who are all English-dominant (average age of L2 acquisition: 3;9), were recruited. They were recorded while reading sentences aloud in Spanish and in English containing laterals in onset and coda positions adjacent to front and back vowels. Target words with laterals were spectrographically analysed through an investigation of F1 and F2 values. The measurements obtained were compared between the two languages. The results show that the participants maintain separate acoustic realizations for the laterals in all four different phonetic environments in their two languages. Since their lateral productions are mixed with respect to the influence of the two languages, the results suggest that bilinguals’ interrelated systems influence each other at a fine-grained acoustic level.